IMPROVING THE ELASTIC MASS OF FIBER ON THE SURFACE OF THE SAW CYLINDER IN FIBER CLEANING EQUIPMENT USING AN ADDITIONAL DEVICE - T, Kuliev; I, Abbazov; F, Egamberdiev (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
In the article in order to improve fiber cleaning equipment, it is proposed to improve the elastic mass of fiber on the surface of the saw cylinder in the equipment using an additional device. The scientific work on the improvement of the equipment was analyzed. In addition, it has been studied that the required 0-2 mm spacing between the clamping brush and the saw cylinder, due to the rapid wear of the clamping brush due to continuous operation of the cleaner, expands to 3-6 mm, and in some cases even more. Inadequate adhesion of the fiber to the saw cylinder, along with the impurities released when the fiber hits the colostrums, the fibers that are weakly attached to the saw teeth are separated into waste. This in turn leads to a decrease in the amount of fiber being produced. To overcome this shortcoming, it is necessary to ensure good adhesion of the fiber to the saw cylinder. For this, the equipment is equipped with a guide device that ensures that the movement of the fiber reaches the surface of the saw blade well, and its effect on cleaning the fiber is theoretically based.